PENGARUH ELECTRONIC WORD OF MOUTH (eWOM) TERHADAP PERILAKU PEMBELIAN IMPULSIF PADA MARKETPLACE SHOPEE - Azizah Hasna' Arifin; Naufal Afif; Meita Dwi Anggraeni; Alfian Chandra Yudiananta; Yesyifa Hanim Kurniavashti (TRANSFORMASI, 2026)
Technological advances have shifted consumer behaviour towards e-commerce platforms, triggering the emergence of impulsive buying or spontaneous shopping without planning. This study aims to analyse the influence of electronic word-of-mouth (eWOM) on impulsive buying behaviour among Shopee marketplace users. The research method used was quantitative, involving the distribution of a questionnaire to 98 Shopee users, most of whom were Generation Z and Millennials aged 21-30. Data dianalisis dengan regresi linier sederhana dan pengujian hipotesis. The results of the study showed that eWOM has a positive and significant influence on impulsive purchases. This is evidenced by the value of the t statistic of 16.633, which is greater than the t table value (1.98498), as well as the significance value of 0.000 < 0.05. The analysis of the determination coefficient showed that eWOM contributes 13.9% to influencing impulsive purchasing decisions. These findings indicate that reviews, ratings, and testimonials from other users are considered credible and persuasive information, thus reducing cognitive barriers and prompting consumers to make spontaneous purchases.